Systematic Review: Anti-Osteoporosis Potential Activities Of Phytoestrogen Compounds In Chrysophyllum cainito L., Elaeis guineensis Jacq., Lannea acida Rich., Marsilea crenata Presl., and Medicago sativa L. - Burhan Ma'arif; Suryanto Suryanto; Faisal Akhmal Muslikh; Arief Suryadinata; Begum Fauziyah (Sanata Dharma University, 2022)
Phytoestrogens are compounds from plants that have a structure and function similar to estrogen (17β-estradiol). Phytoestrogens can be found in Chrysophyllum cainito L., Elaeis guineensis Jacq., Lannea acida Rich., Marsilea crenata Presl., and Medicago sativa L. This systematic review aimed to prove that all of these five plants have phytoestrogens which were observed with several instruments, and to assess activities and bone forming mechanisms from these five plants in the female mice (Mus musculus) and female rats (Rattus norvegicus). This systematic review was done by identifying articles in several databases (Google Scholar, PubMed, and Science Direct). The process of selecting the articles used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to create a flowchart with inclusion and exclusion study criteria. Meta-synthesis was done to analyze, identify, and interpret all of the data in the articles systematically. 31 articles in total were obtained from the selection process, with 27 articles containing a discussion about chemical compound content and 4 articles describing research results for in vivo testing of the plants that were reviewed. The results showed that these five plants have phytoestrogens and by in vivo testing have the activity in increasing trabecular bone density in the experimental animals.